2014
DOI: 10.1007/s40618-014-0185-3
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat, body mass index, and triglyceride are independent contributors of serum fibroblast growth factor 21 level in obese premenopausal women

Abstract: EFT, BMI, and TG may play an important role in predicting serum FGF-21 level which may be a potential therapeutic target in cardiometabolic disorders in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
3
14
0
1
Order By: Relevance
“…The present study supports a significant cross-sectional association between FGF21 levels and pericardial fat volume. In a recent case-control study of 86 post-menopausal women, serum FGF21 levels were positively and significantly correlated with epicardial fat thickness in the obese women 9 . In that study, among different clinical and biochemical parameters including BMI, LDL cholesterol, HDL cholesterol, CRP and HOMA-IR, epicardial fat showed the strongest association with serum FGF21 levels 9 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The present study supports a significant cross-sectional association between FGF21 levels and pericardial fat volume. In a recent case-control study of 86 post-menopausal women, serum FGF21 levels were positively and significantly correlated with epicardial fat thickness in the obese women 9 . In that study, among different clinical and biochemical parameters including BMI, LDL cholesterol, HDL cholesterol, CRP and HOMA-IR, epicardial fat showed the strongest association with serum FGF21 levels 9 .…”
Section: Discussionmentioning
confidence: 93%
“…In model 1, data were adjusted for demographic, socioeconomic and lifestyle factors, including age, sex, race/ethnicity, education, smoking, pack-years of smoking, current alcohol use and physical activity. In model 2, data were further adjusted for established CVD risk, including BMI, diabetes, hypertension, HOMA-IR, high-density lipoprotein (HDL) cholesterol, triglycerides, eGFR, and use of lipid-lowering medication, which have been found to correlate with FGF21 levels in previous studies 5,9,10,13,14 . As FGF21 has anti-inflammatory effects 8 and pericardial fat can secrete pro-inflammatory cytokines 1 , data were further adjusted for circulating inflammatory biomarkers, including CRP and IL-6 in model 3, in order to assess whether these inflammatory biomarkers can mediate the association.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblast growth factor-21 (FGF-21) is a member of the fibroblast growth factor family expressed in multiple organs, such as metabolic organs like the WAT (including EAT and PVAT), liver and pancreas [ 316 , 317 , 318 , 319 ]. It is a secreted protein that acts mainly as an important endocrine metabolism regulator by inducing weight loss and controlling insulin signalling and glucose and lipid metabolism [ 316 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…In fact, some of our previous work shows that various circulating molecules (i.e., adiponectin, TGF b1, e-selectin, and endothelin) play a significant role in left ventricular remodeling [2,3], progression of renal function impairment [4,5], and in the manifestation of left ventricular dysfunction [6][7][8] in central obese subjects. A recent study by Akyildiz et al [9] found that higher serum levels of the hormone FGF 21 were associated with larger epicardial fat thickness in obese women. All the above-mentioned molecules are related to both inflammation and fibrosis at various levels.…”
mentioning
confidence: 95%